An inside job: To get on the right career track, look within - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
While some people may claim to work solely for the money, research has shown 'self-concept' to be an important but often overlooked consideration when choosing between jobs. An out-of-work investment banker may fail to consider 'analyst' positions due to perceptions of job prestige. Similarly, gender stereotypes may prevent a female civil engineering student from considering a career in construction. Speaking at a Behavioural Sciences Institute seminar, Serena Wee, an assistant professor of psychology at SMU, drew links between job seeking behaviours and concepts of identity.